(untitled) (Research, Society and Development, 2021)
To evaluate the knowledge of health professionals in a public teaching hospital about the National Patient Safety Program. Cross-sectional study, applying knowledge questionnaires from the National Patient Safety Program and Hospital Survey on Patient Safety Culture (HSOPSC). Descriptive, univariate and multivariate analyzes were performed. The study included 331 professionals, 44.0% nursing technicians / assistants, 29.7% nurses, 17.1% doctors and 10.5% other professionals. Of the 287 professionals who answered the question about the Program’s knowledge, 78% said they did not know it, almost all (94.5%) were unaware of its six protocols and 90.1% did not receive training on this public policy. Nurses (OR = 15.46; 95% CI = 2.88-82.96) and professionals who held administrative positions with direct contact with the patient (OR = 55.46; 95% CI = 10.23-300.54) if highlighted the knowledge of the existence of the protocols. The degree of knowledge reported by the professionals proved to be insufficient, demonstrating a possible negligence regarding the theme by managers and educators.